INFLUENCE OF THINK TALK WRITE LEARNING MODEL ASSISTED BY PRACTICUM METHOD ON SCIENCE LEARNING OUTCOMES - Latifah Asmul Fauzi; Haslinda Yasti Agustin (Four Son Scholarship, 2024)
The primary objective of this research is to analyze the influence of the Think Talk Write (TTW) learning model assisted by the practicum method on the science learning outcomes, which include the cognitive, affective, and psychomotor abilities of seventh-grade students at SMPN 3 Kalidawir. This study employs a quantitative approach, using a quasi-experimental research type, a non-equivalent control group design, and samples selected through purposive sampling techniques. Data collection is done using pre-test and post-test questions to assess cognitive abilities, questionnaires to evaluate affective abilities, and observations to assess psychomotor abilities. Data analysis uses the Independent Sample T test for data that is normally distributed and homogeneous, while the Mann-Whitney test is used for data that is not normally distributed and homogeneous. The research findings are as follows: (1) there is a positive and significant influence of the Think Talk Write (TTW) learning model assisted by the practicum method on the cognitive abilities, as evidenced by the independent t-test result with a significance value (2-tailed) of 0.003 < 0.05. (2) there is a positive and significant influence of the Think Talk Write (TTW) learning model assisted by the practicum method on the affective abilities, as evidenced by the independent t-test result with a significance value (2-tailed) of 0.002 < 0.05. (3) there is a positive and significant influence of the Think Talk Write (TTW) learning model assisted by the practicum method on the psychomotor abilities, as evidenced by the Mann-Whitney test result with a significance value (2-tailed) of 0.000 < 0.05.